Freedom in the sense of the Heidelberg Catechism - an orientation in the problems of modern liberty - E. Busch (Acta Theologica)
The Heidelberg Catechism courageously mentions that Christians participate in the work of Christ as the eternal king. This means that, during their life on earth, Christians fight against sin “with a free conscience”. These words anticipate the call for human rights in the French Revolution. Although the Catechism uses the word “free” only at this point, the text shows the context in which we have to understand “freedom”. It instructs us that we have to understand the word not as a freedom “from” and, therefore, not as freedom only for myself, but as freedom “for” a life with others. The reason for this is that real freedom is founded in the gift of the divine liberator, who loves us only along with our neighbours. We are free in relation to God and our fellow human beings.